The Association between COVID-19 Vaccine Types and Side Effects Following Vaccination: Cross-Sectional Study - Alifia Maharani Setyoputri; Chandrayani Simanjorang; Laily Hanifah; Ulya Qoulan Karima (Media Kesehatan Masyarakat Indonesia, 2023)
Many experts agree and believe that the COVID-19 vaccine is the best way to control the COVID-19 pandemic in a sustainable manner. Each type of vaccine has different side effects and effectiveness. Meanwhile, information regarding the relationship between the type of COVID-19 vaccines and side effects in real populations, especially in Indonesia, is still limited. The aim of this study was to investigate the association between COVID-19 post-vaccination side effects and COVID-19 vaccine type. From April to June 2022, a cross-sectional quantitative study will be conducted in Bekasi City, West Java, Indonesia. The population consists of all 1,885,014 residents of Bekasi City who have received the first dose of COVID-19 vaccination. The samples obtained were 428 respondents from online surveys employing a purposive sampling technique. Among 428 participants, there were 50.50% received Inactivated Virus (Sinovac/Sinopharm), 23.80% Viral Vector (AstraZeneca), and 25.70% mRNA (Moderna/Pfizer-BioNTech). The adjusted analysis showed a significant correlation between the type of viral vector vaccine (OR: 26.60; 95% CI: 11.04-64.30) and the type of mRNA vaccine (OR: 1.80; 95% CI: 1.17-3.04) with side effects of COVID-19 vaccination. There was a correlation between the type of vaccines with side effects after controlled variables of sex and history of infection.